1992
DOI: 10.1159/000196022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Respiratory and Circulatory Human Responses to Progressive Hypoxia and Hypercapnia

Abstract: The effects of acute, progressive isocapnic hypoxia and hyperoxic hypercapnia on lung ventilation, heart rate, cardiac output and arterial blood pressure were determined simultaneously in 32 normal individuals. All subjects were exposed to hypoxia and hypercapnia in an entire range of individual tolerance. The piecewise linear approximation technique was used for analysis of the ventilatory and circulatory response curves. In all subjects, the changes in hemodynamics in the response to hypoxia paralleled those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Also, there is an interaction between the baroreceptors and the chemoreflex responses to hypoxia (39). Concerning hemodynamic response to progressive isocapnic hypoxia developed in parallel to ventilatory response, Serebrovskaya (37) assumed that parallel reflex reactions of respiration and circulation may be induced by the impulses from the peripheral chemoreceptors sensitive to the hypoxia simultaneously reaching the respiratory and vasomotor centers. From several reports mentioned above, because the mechanism of BP response to hypoxia is complicated and the significant correlations between ␦HVR and ␦⌬SBP/⌬Sa O 2 by endurance training and detraining cannot establish cause and effect, it cannot be proved that the changes in the SBP response in the present study are simply induced by the changes in ventilatory response to hypoxia as proposed by Insalaco et al (15), but it seems reasonable to suppose that there is an interaction between the changes in the SBP and ventilatory responses to isocapnic hypoxia by endurance training and detraining.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is an interaction between the baroreceptors and the chemoreflex responses to hypoxia (39). Concerning hemodynamic response to progressive isocapnic hypoxia developed in parallel to ventilatory response, Serebrovskaya (37) assumed that parallel reflex reactions of respiration and circulation may be induced by the impulses from the peripheral chemoreceptors sensitive to the hypoxia simultaneously reaching the respiratory and vasomotor centers. From several reports mentioned above, because the mechanism of BP response to hypoxia is complicated and the significant correlations between ␦HVR and ␦⌬SBP/⌬Sa O 2 by endurance training and detraining cannot establish cause and effect, it cannot be proved that the changes in the SBP response in the present study are simply induced by the changes in ventilatory response to hypoxia as proposed by Insalaco et al (15), but it seems reasonable to suppose that there is an interaction between the changes in the SBP and ventilatory responses to isocapnic hypoxia by endurance training and detraining.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, 2 weeks of IHT increased the hypoxic ventilatory response, which was taken to indicate an increased hypoxic responsiveness of the carotid body with altitude acclimatization. Examination of the time course has suggested that the enhancement of ventilatory sensitivity begins with the first hypoxic exposure, and approaches a plateau by the third day (Serebrovskaya, 1992;Serebrovskaya and Ivashkevich, 1992). If so, then in normal humans only a few minutes of daily hypoxic exposure rapidly induces detectable increments in hypoxic ventilatory response, a hallmark of altitude acclimatization.…”
Section: Intermittent Hypoxic Training and Ventilationmentioning
confidence: 99%
“…In men, acute hypercapnia leads to a pressor response in the systemic circulation (14,15,17), which is at least partially mediated via an increased sympathetic tone (17), but this response has not been reported in female subjects. The purpose of this study was to investigate the pressor effect of acute hyperoxic hypercapnia during the normal menstrual cycle.…”
mentioning
confidence: 96%